Improving Students' Religious Attitudes through Fiqh Learning at MTs Al-Islamiyah Bebidas - Lalu Hasroni (BAYAN: Jurnal Studi Islam dan Humaniora, 2026)
This study aims to improve students’ religious attitudes through Fiqh learning using a Classroom Action Research (CAR) approach at MTs Al-Islamiyah Bebidas. The religious attitudes examined include discipline in worship, honesty, responsibility, social awareness, and learning engagement. This research employed the Classroom Action Research design based on the Kemmis and McTaggart model, consisting of planning, action, observation, and reflection stages. The research subjects were eighth-grade students of MTs Al-Islamiyah Bebidas. The study was conducted in two cycles. Data were collected through observation, questionnaires, and documentation, and analyzed using descriptive qualitative and quantitative techniques. The results indicate a significant improvement in students’ religious attitudes from the pre-action stage to the second cycle. The average level of religious attitudes increased from a low category in the pre-action stage to a moderate category in Cycle I and reached a good category in Cycle II. These findings demonstrate that contextual and applicable Fiqh learning implemented through Classroom Action Research is effective in improving students’ religious attitudes.